2014
DOI: 10.1007/s11096-014-9976-z
|View full text |Cite
|
Sign up to set email alerts
|

Potential drug related problems detected by electronic expert support system in patients with multi-dose drug dispensing

Abstract: Background Drug related problems (DRPs) are frequent and cause suffering for patients and substantial costs for society. Multi-dose drug dispensing (MDDD) is a service by which patients receive their medication packed in bags with one unit for each dose occasion. The clinical decision support system (CDSS) electronic expert support (EES) analyses patients' prescriptions in the Swedish national e-prescription repository and provides alerts if potential DRPs are detected, i.e. drug-drug interactions, duplicate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 44 publications
0
15
0
5
Order By: Relevance
“…EES is a government-owned CDSS that analyses patients´ electronically stored prescriptions in the Swedish national prescription repository. It was originally developed by Medco Health Solutions in the US and has been adapted to Swedish clinical practice [ 25 ]. EES is available to Swedish pharmacies and is developed and maintained by the Swedish eHealth Agency.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…EES is a government-owned CDSS that analyses patients´ electronically stored prescriptions in the Swedish national prescription repository. It was originally developed by Medco Health Solutions in the US and has been adapted to Swedish clinical practice [ 25 ]. EES is available to Swedish pharmacies and is developed and maintained by the Swedish eHealth Agency.…”
Section: Methodsmentioning
confidence: 99%
“…EES is not available to prescribers in Swedish health care. Previous studies have described the potential DRPs detected by EES in patients with multi-dose drug dispensing and have shown that physicians regard the majority of alerts as clinically relevant [ 25 , 26 ]. Although EES has been available at pharmacies for many years, its use has been low and only studied in a few small studies where most of them are not published scientifically [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…17 Several systems have been proposed for the classification of DRP, with the Pharmaceutical Care Network Europe (PCNE) being one of the most commonly used classification systems in hospital practice. 18 Several DRP detection strategies have been developed, including pharmacist review of medication orders (MO), the use of computerised physician order entry (CPOE) systems couple with clinical decision support programs [19][20][21] that allow the clinical pharmacist to have an active participation within the healthcare team. 5 8 22-24 However, despite the clinical and economic relevance of DRP, very few studies have investigated the incidence, types and causes of DRP in patients hospitalised in general medical and surgical wards.…”
Section: Introductionmentioning
confidence: 99%
“…Improper doses primarily identified in geriatric and pediatric patients' prescription. The study by Tora et al (2014) shows that the warning category for potential DRPs frequently identified by EES/CDSS in the age group >65 years old is drug-drug interaction with drug (38.6%), geriatric warning (30.8%), and duplications of therapy (25.6%). The geriatric warning includes warning in drug inaccuracies in the elderly (11% warning), extremely high doses (9%), and more than 3 types of psychotropic drug (3%) (Table 4) [4].…”
Section: The Number and Types Of Drpsmentioning
confidence: 99%
“…Thereby, that the information technology in treatment management process has been suggested to improve appropriate and safe treatment. The utilization of computerized-based information technology is proven to efficiently assist the pharmacists in identifying potential DRPs [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%